Primary screening of blood donors by nat testing for HCV-RNA: development of an "in-house" method and results - Wendel, Silvano; Levi, José Eduardo; Takaoka, Deise Tihe; Silva, Isabela Cristina; Castro, Juliana Polachini de; Torezan-Filho, Mário A.; Ghaname, Jorge; Gioachini, Romualdo; Brandão, Joselito; Durigon, Edison Luis (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
An "in-house" RT-PCR method was developed that allows the simultaneous detection of the RNA of the Hepatitis C Virus (HCV) and an artificial RNA employed as an external control. Samples were analyzed in pools of 6-12 donations, each donation included in two pools, one horizontal and one vertical, permitting the immediate identification of a reactive donation, obviating the need for pool dismembering. The whole process took 6-8 hours per day and results were issued in parallel to serology. The method was shown to detect all six HCV genotypes and a sensitivity of 500 IU/mL was achieved (95% hit rate). Until July 2005, 139,678 donations were tested and 315 (0.23%) were found reactive for HCV-RNA. Except for five false-positives, all 310 presented the corresponding antibody as well, so the yield of NAT-only donations was zero, presenting a specificity of 99.83%. Detection of a window period donation, in the population studied, will probably demand testing of a larger number of donations. International experience is showing a rate of 1:200,000 - 1:500,000 of isolated HCV-RNA reactive donations.